YouTube Comments Analyzer Using Natural Language Processing And Artificial Intelligence - Lonkar, Trupti; Katkar, Tejali; Karajgar, Manasi; Lonkar, Ganesh; Shelar, Shradha (International Journal of Computer Sciences and Engineering, 2024)
The exponential growth of online video content has propelled YouTube to the forefront of digital media platforms, where creators and viewers converge in a vibrant ecosystem. However, amidst the proliferation of videos, the accompanying surge in viewer comments poses a significant challenge for content creators and researchers alike. Manually sifting through this deluge of comments to gauge sentiment and understand audience feedback is increasingly untenable. To address this challenge, this manuscript introduces an automated tool, the YouTube Comment Analyzer, designed to efficiently extract and analyze comments on YouTube videos, categorizing them based on sentiment.